ECONOMIC CHALLENGES AND POTENTIALS FOR SUSTAINABLE DEVELOPMENT IN RURAL AREAS OF SERBIA - Vladan Vučić; Dejan Dašić; Milica Mladenović (Ekonomika Poljoprivrede (1979))
Rural areas of Serbia face serious economic challenges, including depopulation, low levels of investment, and limited access to infrastructure. Nevertheless, these areas also possess significant potential for sustainable development, particularly in agriculture, renewable energy, rural tourism, and digital transformation. The key to improving the economic position of these regions lies in the integration of sustainable development policies that promote local entrepreneurship, preserve natural resources, and enhance the quality of life for the population. This paper analyzes the existing problems, identifies key potentials, and proposes development directions that could contribute to the long-term economic and social recovery of rural communities in Serbia.